2018
DOI: 10.5897/ijps2018.4733
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and geochemical properties of clay deposits in parts of Southeastern Nigeria

Abstract: The rocks underlying many parts of Southeastern Nigeria had undergone extensive alterations to form considerable clay deposits. The mineralogical compositions of some of these clay deposits were evaluated with the X-Ray Diffraction (XRD) method to ascertain the suitability of the deposits as raw materials. Results of the analyses indicated that kaolinite (Al 2 Si 2 O 5 (OH) 4 ) is the dominant clay mineral. Traces of bentonite and dickite were also observed, while the identified non-clay minerals were quartz a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Also, the chemical index of alteration (CIA) proposed by Nesbitt and Young [34], was calculated for the studied samples to establish the extent of alteration/weathering. The CIA varied from (75-97%), this indicates reduction in the contents of alkali and alkaline earth elements (Table 2), as recorded from the studied clays, typically suggesting a relatively intense weathered source area [7]. The significant presence of kaolinite in the investigated clays could undoubtedly lead to poor rheological properties since such type of clay has low swelling capability.…”
Section: Chemical Compositionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Also, the chemical index of alteration (CIA) proposed by Nesbitt and Young [34], was calculated for the studied samples to establish the extent of alteration/weathering. The CIA varied from (75-97%), this indicates reduction in the contents of alkali and alkaline earth elements (Table 2), as recorded from the studied clays, typically suggesting a relatively intense weathered source area [7]. The significant presence of kaolinite in the investigated clays could undoubtedly lead to poor rheological properties since such type of clay has low swelling capability.…”
Section: Chemical Compositionsmentioning
confidence: 72%
“…Meanwhile, several clay deposits have been discovered, their industrial uses investigated and reported in Nigeria [1][2][3][4][5][6][7] These deposits range from lateritic/residual clays from weathered products of basement complexes [3,4,7] to those arising from sedimentary units within the various sedimentary basins, as well as those formed along major river channels [1,5,6]. A survey carried out by the Nigerian Mining Corporation typically established the presence of bentonitic clay reserves of over 700 million tonnes within Nigeria, with the largest deposit found in Afuze, Edo State, estimated at 70-80 million tonnes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The study area, which lies within the geographical coordinates [4]. The average annual rainfall is about 2400mm and there is a distinct dry season of about 3-month dryness.…”
Section: Materials and Methods 21 Study Areamentioning
confidence: 99%
“…Pavement failure issues include cracking, potholes, depressions, rutting, shoving, upheavals, and raveling [1]. Source: Mineralogical and geochemical properties of clay deposits in parts of Southeastern Nigeria, [4] Sometimes, the defective pavement and unstable surfacing materials are removed down to a stable base before overlaying with new materials. Sooner than later these remedial works are done, pot holes and rutting usually resurface.…”
Section: Introductionmentioning
confidence: 99%
“…However, they recommended that the Cretaceous Lakiri kaolins can be used in the paper and ceramic industry (except for kaolins having high TiO 2 and K 2 O content). [32] used XRD to evaluate the suitability of clay mineral as raw material in Ikpankwu, Okigwe down to Ohiya in the Okigwe-Umuahia axis. Results from the study showed that the clays are mainly kaolins; with traces of bentonite and dickite, non clay mineral content included quartz and iron.…”
Section: Literature Review On Clay Mineral Across Southern Part Of Nigeriamentioning
confidence: 99%